Kierunki rozwoju systemów jakości w niemieckim przemyśle samochodowym na przykładzie VOLKSWAGEN Motor Polska w Polkowicach - Bobik, Dorota (Directions in quality systems development in German automobile manufacturing based on VOLKSWAGEN Motor Poland in Polkowice, 2006)
The automobile industry has always been a leader in the quality management area. Analyzing actions taken in the German enterprise VOLKSWAGEN Motor Poland belonging to Volkswagen AG Company, many various directions in management systems in automobile industry can be observed. VW’s quality is certified and our engines receive the so-called type-acknowledgement and trafficpass. ISO 9001 and branch standards are the basis for this certification. Both VDA 6.1 and ISO 16 949 were created on the basis of ISO 9001 but include more requirements than the latter standard. The quality management systems certified on the basis of VDA 6.1 or ISO 16 949 are continuously evolving towards perfection in business and manufacturing. This perfection is based on the prior regulations, i.e. Eight Excellence Rules, EFQM Model, and quality awards system participation and helps to initiate improving actions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 269-281